Legalitas Poligami; Studi Atas Aturan Praktik Poligami diberbagai Negara Islam : (Turki, Syiria, Somalia, Mesir, Tunisia dan Indonesia) - Luthfiyah, Luthfiyah; Al-Farisyi, Ali Imron (ASASI: Journal of Islamic Family Law, 2022)
This article examines the existence of laws and regulations from various Islamic countries (only part of them). The study carried out is the existence of polygamy practices in various countries based on juridical law which is used with the aim of wanting to know the extent to which the implementation of the polygamy law is binding on each community with adherents of different religions and social conditions. The method used in this research is a normative juridical research with a statute approach. The results of this study indicate that there are fundamental differences from each country as an example, such as Indonesia, which is not an Islamic country, so it does not emphasize polygamy for its people, apart from that the principle of monogamy takes precedence. The difference is with the country of Somalia which is so loose in the practice of polygamy.